2003
DOI: 10.1097/01.ju.0000052680.03705.40
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Of Sclerotherapy With Phenol and Surgical Treatment for Hydrocele

Abstract: Sclerotherapy for hydrocele with phenol is as efficacious as hydrocelectomy, while causing less morbidity and similar effects on spermatogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 13 publications
6
20
0
1
Order By: Relevance
“…In the present study the mean hydrocele volume (212.9 ml) is comparable to the mean volume reported in other [3,[5][6][7]. The volume of phenol instilled by us is in accordance with the studies of Shan et al in which volume of phenol instilled was proportional to the volume of the hydrocele [3].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…In the present study the mean hydrocele volume (212.9 ml) is comparable to the mean volume reported in other [3,[5][6][7]. The volume of phenol instilled by us is in accordance with the studies of Shan et al in which volume of phenol instilled was proportional to the volume of the hydrocele [3].…”
Section: Discussionsupporting
confidence: 95%
“…This was followed by injection of 5-10 ml of 5% aqueous phenol or 2-4 ml of 1% polidocanol. The respective volumes were selected on the basis of the studies of Shan et al and Sigurdsson et al for phenol and polidocanol, respectively [3,4]. In none of the cases a second injection of the sclerosant was given.…”
Section: Patient and Methodsmentioning
confidence: 99%
“…In our earlier research, in a study which compared hydrocelectomy with sclerotherapy we found a slight reduction in the concentration of sperm per milliliter at 6th and 12th months, with no statistical significance. The reduction occurred on both groups that underwent sclerotherapy or hydrocelectomy (11). In this present study we found a reduction in the parameters up to 6t months, with no statistical significance, but at the 12th month these abormalities returned to baseline parameters.…”
Section: Sclerotherapy Of Hydroceles and Spermatocelessupporting
confidence: 49%
“…Reported complications in the hydrocelectomy group were edema, hematoma, wound infection, cellulites in 2, 5, 2 and 1 cases of 24 patients, respectively. Although sclerotherapy allows patients to return to normal activity on the same day, requirement for multiple injections is the limitation of the procedure [7]. Endoscopic hydrocelectomy, another minimally invasive technique in the treatment of hydroceles, was first described by Ho GT in a single case, in 1992 [1].…”
Section: Discussionmentioning
confidence: 99%